Architecture of β‐Graphdiyne‐Containing Thin Film Using Modified Glaser–Hay Coupling Reaction for Enhanced Photocatalytic Property of TiO2. Issue 19 (15th March 2017) - Li, Jiaqiang; Xie, Ziqian; Xiong, Yan; Li, Zhenzhu; Huang, Qunxing; Zhang, Shuqing; Zhou, Jingyuan; Liu, Rong; Gao, Xin; Chen, Changguo; Tong, Lianming; Zhang, Jin; et al.
Abstract : β‐Graphdiyne (β‐GDY) is a member of 2D graphyne family with zero band gap, and is a promising material with potential applications in energy storage, organic electronics, etc. However, the synthesis of β‐GDY has not been realized yet, and the measurement of its intrinsic properties remains elusive. In this work, β‐GDY‐containing thin film is successfully synthesized on copper foil using modified Glaser–Hay coupling reaction with tetraethynylethene as precursor. The as‐grown carbon film has a smooth surface and is continuous and uniform. Electrical measurements reveal the conductivity of 3.47 × 10 −6 S m −1 and the work function of 5.22 eV. TiO2 @β‐GDY nanocomposite is then prepared and presented with an enhancement of photocatalytic ability compared to pure TiO2 . Abstract : A modified Glaser–Hay coupling reaction is used to synthesize β‐graphdiyne‐containing thin film . Copper foil plays the role of both a substrate and the source of catalyst. The as‐grown film is with conductivity property and can be applied to enhance the photocatalytic property of TiO2 .